13.08: Plastic resistance of U sections under major‐axis bending, shear force and bi‐moments. (13th September 2017) - Beyer, André; Khelil, Abdelouahab; Boissonnade, Nicolas; Bureau, Alain
ABSTRACT: Eurocode 3 Part 1–1 gives several specific plastic cross‐section interaction equations for I sections. However, the case of U sections is not explicitly addressed. In order to overcome these limitations, an extensive numerical parametric study has been conducted. So as to obtain realistic plastic section resistances, material non‐linear analyses (MNA) have been performed on a numerical model of U‐shaped members modelled with Solid (volume) Finite Elements. In the present paper, the most practical case of U sections subjected to a combination of major‐axis bending, shear force and a bi‐moment (resulting from the torsional load) is treated and a simplified interaction formula is derived. Additionally, it will be shown that the complex torsional behaviour of open cross‐sections leads to a supplementary plastic system for members made of U sections.